THE ENZYMATIC ACTIVITY CHANGES DURING THE DEVELOPMENT OE SOILS (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Activity of enzymes of different samples of the virgin, weakly and powerful cultivated rock semi-desert and brown soils was investigated. It is stated that the ecological factors, which determine the soils' biological activity, are changed during the soils' cultivation. It may be proved by the enzyme activity determination. During soils' cultivation the activity of enzymes is submitted to regular changing, hence it may be used as an exponent of the level of soils' cultivation.